The influence of a doppler ultrasound in arteriovenous fistula for dialysis failure related to some risk factors - Lopes,Jocefábia Reika Alves (2020)
ABSTRACT Introduction: The increasing prevalence of chronic kidney disease has increased the demand for arteriovenous fistula (AVF) care. The objective of this study was to assess the relationship between some risk factors for AVF failure (advanced age, female sex, diabetes, obesity, central venous catheter, previous fistula, and hospitalization) and having a Doppler ultrasound performed preoperatively. Methods: A prospective study was performed with 228 dialysis patients from Imperatriz, Maranhão. Half of the sample was randomly selected to receive preoperative Doppler ultrasound and the other half did not, from the period of October 2016 to September 2018. Results: There were 53 total failures corresponding to 23.2% of our sample, which is almost double that of the patients in the clinical group. Considering the failures and risk factors associated with the overall sample, there was a statistically significant association between a central venous catheter on the same side of the AVF with P = 0.04 (Odds Ratio 1.24) and obesity with P = 0.05 (Odds Ratio 1.36), which was not repeated in the Doppler ultrasound group individually. There was no statistically significant difference between the Doppler group and clinical group with respect to the amount of days of previous AVF hospitalization and failure. Conclusions: We concluded that the reduction of failures with an introduction of the Doppler was statistically significant in the overall sample, but establishing a relationship between specific risk factors and failure was only possible with two of the risk factors in the study - obesity and central venous catheter on the same side of the AVF.